Starch sources and their influence on extrusion parameters, kibble characteristics and palatability of dog diets - Gislaine Cristina Bill Kaelle; Taís Silvino Bastos; Renata Bacila Morais dos Santos de Souza; Eduarda Lorena Fernandes; Lorenna Nicole Araújo Santos; Simone Gisele de Oliveira; Ananda Portella Félix (Italian Journal of Animal Science, 2024)
This study aimed to evaluate the effects of different starch sources on the extrusion process, kibble characteristics and diet palatability for dogs. Seven diets with corn, brown rice, sorghum, potato starch, sweet potato flour, chickpea and pea as the only starch source were evaluated. The dietary inclusion of the starch sources varied between 330.13 and 643.84 g/kg to provide similar starch concentrations in all diets (around 300 g/kg). The conditioning temperature and the volume of water added to the preconditioner during the processing of the diets were measured, and the extruder variables evaluated were knife speed, feed rate, screw speed, amperage and productivity. For the physical characteristics of kibbles, density, size, expansion index and hardness were measured. Porosity variables evaluated were total pore area, average pore area and number of pores. Diet palatability was evaluated in 16 dogs. Six paired palatability tests were performed, in which all diets were compared to the corn diet, with two consecutive days per test, totalling 32 repetitions (16 dogs × 2 days/test). Diets with tubers presented lower kibble density and higher size, expansion index and hardness than the diets with cereals and pulses (p < 0.001). Diets with tubers had more pores than pulses (p < 0.001). The inclusion of pea results in kibbles that were less expanded and with fewer pores (p < 0.001). Dogs preferred all diets compared with the corn-based diet (p < 0.001), except for the sweet potato diet. The dietary inclusion of tubers as starch sources results in higher kibble expansion, size, hardness, porosity and lower density. The inclusion of pea results in kibbles that are less expanded and with a lower number of pores. The diet’s moisture content and texture affect diet palatability in dogs.